2013
DOI: 10.1016/j.jbiomech.2013.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Azidothymidine (AZT) leads to arterial stiffening and intima-media thickening in mice

Abstract: HIV positive patients on highly active antiretroviral therapy (HAART) have shown elevated incidence of a number of non-AIDS defining co-morbidities, including cardiovascular disease. Given that HAART regimens contain a combination of at least three drugs, that disease management often requires adjustment of these regimens, and HIV, independent of HAART, also plays a role in development of co-morbidities, determining the role of specific HAART drugs and HIV infection itself from clinical data remains challengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Therefore, it may be that an important contribution to the variability in breast cancer cell invasion and tumor growth and spread may be due to the TAMs that infiltrate, and locally secrete cathepsins and cystatin C that can directly assist cancer cell invasion. As a predictive metric, this holds promise by providing insight into the importance of biomarkers in the local tumor microenvironment as opposed to studies that have sought metastatic correlation after serum measurement of cathepsins or cystatin C 51 52 53 . Cathepsins in serum may be from a number of sources, including cardiovascular sources for which cathepsin levels have been correlated with atherosclerosis, diabetes, and abdominal aortic aneurysms 54 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be that an important contribution to the variability in breast cancer cell invasion and tumor growth and spread may be due to the TAMs that infiltrate, and locally secrete cathepsins and cystatin C that can directly assist cancer cell invasion. As a predictive metric, this holds promise by providing insight into the importance of biomarkers in the local tumor microenvironment as opposed to studies that have sought metastatic correlation after serum measurement of cathepsins or cystatin C 51 52 53 . Cathepsins in serum may be from a number of sources, including cardiovascular sources for which cathepsin levels have been correlated with atherosclerosis, diabetes, and abdominal aortic aneurysms 54 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Zidovudine (3-azido-3′-deoxythymidine or AZT), a nucleoside reverse transcriptase inhibitor, was the first HAART drug approved by the U.S. Food and Drug Administration for treatment of patients with AIDS, and is still the backbone of the large proportion of HAART treated patients in the developing world where majority of HIV infected patients resides [4]. However, the clinical effectiveness of AZT is constrained due to its adverse side effects [5]; the most common of which is hepatotoxicity [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…One HIV-negative control patient was loaded in each zymogram for normalization across gels. The initial hypothesis was that HIV-positive individuals on ART would have higher cathepsin activity in support of the data that ART leads to increased cardiovascular disease (21, 22), and cathepsins are elevated in cardiovascular disease (1420). However, the results clearly indicated that a majority of the patients on ART had suppressed cathepsin activity compared to the HIV-positive, ART naïve patients or the HIV-negative control, as shown in the representative zymogram by the cleared white bands that indicate active cathepsins (Figure 1A).…”
Section: Resultsmentioning
confidence: 89%